Multimedia courseware for interactive teaching and learning: students’ needs and perspectives - Nur Yunus, Faizal Amin; Md. Omar, Noor Hafiza; Sulaiman, Junita; Rahim, Mohd Bekri; Abd Baser, Jamil; Kamis, Arasinah; Mohd Affandi, Haryanti (Penerbit UTHM, 2020)
Education faces many new challenges in meeting the demands of teaching and learning for the 21st century. One of the new challenges is to integrate ICT (Information and communication technologies) in teaching and learning as a means of delivering alternative teaching. Multimedia technology, for example, has the potential to transform a traditional classroom into an unlimited imaginary world. This paper report on development and evaluation of a multimedia courseware for Design and Technology (RBT). An interactive CD was developed using the Adobe Flash CS6 software. Alpha and Beta testing have been carried out in the development process. 6 experts were assigned to evaluate the functionality of the interactive CD. In order to identify the usability of interactive CD, 103 respondents were involved in the survey by filling four-point Likert scaled questionnaire. The findings show that, the level of interactive CD usability is at a high level. Based on this study, there are positive effects that we can see based on the use of multimedia elements in the education system. The meaningful benefits of using multimedia elements for learning include the presentation of various learning styles. The presentation of information usually integrates multimedia elements such as text, graphics, audio and video.